2013
DOI: 10.3758/s13414-012-0404-y
|View full text |Cite
|
Sign up to set email alerts
|

Foreign accent strength and listener familiarity with an accent codetermine speed of perceptual adaptation

Abstract: We investigated how the strength of a foreign accent and varying types of experience with foreignaccented speech influence the recognition of accented words. In Experiment 1, native Dutch listeners with limited or extensive prior experience with German-accented Dutch completed a cross-modal priming experiment with strongly, medium, and weakly accented words. Participants with limited experience were primed by the medium and weakly accented words, but not by the strongly accented words. Participants with extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
126
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(130 citation statements)
references
References 41 publications
3
126
0
1
Order By: Relevance
“…In addition, the nonnative Dutch listener data suggest that experience with foreign-accented speech in one language (i.e., Italian-accented Dutch) can lead to benefits in recognizing accented words in another language (Italian-accented English). Long-term prior experience with accented speech thus establishes a phonetic-to-lexical mapping that can be applied not only to new speakers of that accent (as previously shown by Witteman et al, 2013) but also to speakers of similar accents in other languages. Third, long-term experience with multiple languages (and probably also with multiple accents) plays another role in determining the flexibility of listeners' responses to foreign-accented speech.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…In addition, the nonnative Dutch listener data suggest that experience with foreign-accented speech in one language (i.e., Italian-accented Dutch) can lead to benefits in recognizing accented words in another language (Italian-accented English). Long-term prior experience with accented speech thus establishes a phonetic-to-lexical mapping that can be applied not only to new speakers of that accent (as previously shown by Witteman et al, 2013) but also to speakers of similar accents in other languages. Third, long-term experience with multiple languages (and probably also with multiple accents) plays another role in determining the flexibility of listeners' responses to foreign-accented speech.…”
Section: Resultsmentioning
confidence: 80%
“…If the arbitrariness of a mispronunciation matters to listeners, then they should fail to recognize forms in foreign-accented speech which are arbitrary in the accent they are listening to (e.g., an Italian shortening the stressed vowel in eatery to Itary) but may succeed if the forms are a genuine feature of that accent (e.g., an Italian lengthening the stressed vowel in Italy to Eataly). Indeed, for genuine variant forms, Witteman, Weber, and McQueen (2013) have recently shown that listeners can recognize genuine variants forms when listeners are familiar with the accent or when accent strength is moderate (see also Weber, Broersma, & Aoyagi, 2011). In order to investigate the role of genuineness further, we compared the recognition of foreign-accented words with genuine accent markers with that of foreign-accented words with arbitrary accent markers.…”
Section: Genuinely-accented Vs Arbitrarily-accented Pronunciationsmentioning
confidence: 99%
“…Given evidence for rapid adjustment to non-standard pronunciations in priming tasks (Witteman, Weber, & McQueen, 2013), we examined whether the patterns of priming changed over time. An analysis comparing the priming effects created by accented primes in the first half of the experiment was not different from the corresponding priming in the second half.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we demonstrated the same with Chinese-accented English words, showing that the distances of both F1 and F2 values from typical native productions positively correlate with the strength of perceived accentedness. Also, as was suggested by Witteman et al (2013), deviations in vowel quality appear to be a driving force in the perception of foreign accentedness. On the basis of the ΔAIC results, it appears that the interaction between the log F1 and log F2 distances is quite important in the assessment of foreign accentedness.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that accentedness ratings (for various L1-L2 combinations) can be predicted by many of the acoustic variables discussed above (Munro, 1993;Porretta & Tucker, 2012;Wayland, 1997). Witteman, Weber, and McQueen (2013) stated that vowels drive differences in perceived accentedness because they can vary significantly from standard forms, and Munro (1993) showed this for L1 Arabic productions of English vowels. In that study, five native English-speaking listeners (all linguists) rated the accentedness of vowel productions from native Arabic speakers.…”
mentioning
confidence: 99%